Between empires Arabs, Romans, and Sasanians in late antiquity - Fisher, Greg 1976- (Oxford Oxford University Press, 2011)
An examination of the complex inter-relationships between the Roman and Sasanid Empires, and some of their Arab allies and neighbours, during the last century before the emergence of Islam. Greg Fisher stresses the importance of a Near East dominated by Rome and Iran for the formation of early concepts of Arab identity
Includes bibliographical references and index
Keywords: Sassanids; Iran ; Relations ; Rome; Rome ; Relations ; Iran; Iran ; History ; To 640; Rome -- Relations -- Iran; Iran -- History -- To 640; Iran -- Relations -- Rome